ANALYSIS OF THE TRAINING NEEDS IN RENEWABLE ENERGY SOURCES FOR AGRICULTURAL SECTOR - Zuzana PALKOVA; Ioannis HATZILYGEROUDIS; Sorin IONIŢESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2014)
Global climate changes, the greenhouse gas emissions and reduced sources of traditional fossil fuels are one of themost serious environmental problems of present time. This fact was the starting point for Directive 2009/28/EC,which defined two objectives in the area of RES, the mandatory 20% share of RES in gross final energyconsumption in the European Community and the mandatory 10% share of RES in transport, which all MemberStates must achieve by 2020. In 2011 was the share of renewable energy sources in total energy production in theEuropean Union 13%. Promoting the use of renewable sources for electricity, heat, hot water, as well as promotingthe use of biomass energy and construction of energy efficient buildings brings, in addition to environmentalaspects, the development of innovative technologies, the transition to an energy-efficient economy and increaseemployment opportunities. Development in clean technologies becomes a strategic not only in terms of ecology, buthas a significant impact on economic development and employment. This paper presents an analysis of trainingneeds in clean technologies and renewable energy sources and through the Leonardo da Vincis’ projects – AVARESand C-TEST – supported by European Commission to show how to increase the attractiveness and accessibility ofvocational education and training for employees in agricultural sector in the European Union.